When and where does near-surface runoff occur in a pre-Alpine headwater catchment? - V. A. Gauthier; A. Leuteritz; I. van Meerveld (Hydrology and Earth System Sciences)
Although runoff processes have been described for many locations worldwide, there has been a lack of studies for poorly drained soils where most of the runoff may occur near the soil surface. Therefore, in this study, we aimed to improve the understanding of near-surface processes across a small headwater catchment with low-permeability gleysols that is typical for the Swiss pre-Alpine region. We installed 14 small (1 m×3 m) bounded runoff plots to collect overland flow (including biomat flow; OF) and shallow subsurface flow through the topsoil, which we refer to as topsoil interflow (TIF). The runoff plots were located at different topographic positions and had a range of vegetation covers. For 27 rainfall events during the summer of 2022, we determined the occurrence and amount of OF and TIF. OF and TIF occurred for approximately half of the events, but the frequency of occurrence depended on the topographic wetness index (TWI) and vegetation cover of the plot. The runoff ratios (ratio between total runoff and total precipitation) were highly variable and were generally higher for TIF than for OF. They increased with increasing precipitation and antecedent-wetness conditions but were not correlated with the rainfall intensity. Runoff ratios for OF were larger than 1 for some plots, indicating the occurrence of return flow from outside the plot. The runoff ratio did not change after removing the upper boundary of the plot, suggesting that the actual flow path lengths over the surface are short. Overall, this study highlights the importance of fast near-surface processes in pre-Alpine catchments underlain by low-permeability gleysols and the fact that these processes occur across a range of catchment locations and land covers.